2006
DOI: 10.1203/01.pdr.0000228326.99650.19
|View full text |Cite
|
Sign up to set email alerts
|

Local Shwartzman Reaction in the Rat Induced by Endotoxin and Ischemia: Potential Model for Skin Necrosis in Meningococcemia

Abstract: ABSTRACT:The local Shwartzman reaction (LSR) is an inflammatory response in the skin that is considered a model for skin necrosis associated with meningococcemia. We tested the hypothesis that ischemia can act as the provocative agent to produce this response. In eight rats, bilateral inferior epigastric flaps were outlined. Within each flap, three injection sites were marked. Site 1 had 0.1 mL of endotoxin injected 24 h before surgery. The other two sites had either endotoxin or saline injected immediately be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…The most important skin pathologic findings in the experimental cutaneous Shwartzman are vastly skin necrosis, vascular thrombosis, hemorrhage, and infiltration of leukocytes, especially neutrophils, into the site of inflammation 3,7,27 . In the current study, skin pathologic findings showed a slight skin necrosis and neutrophils recruitment in group treated with 100 pmol of trimer aptamer (Figure 7(a)).…”
Section: Resultssupporting
confidence: 54%
“…The most important skin pathologic findings in the experimental cutaneous Shwartzman are vastly skin necrosis, vascular thrombosis, hemorrhage, and infiltration of leukocytes, especially neutrophils, into the site of inflammation 3,7,27 . In the current study, skin pathologic findings showed a slight skin necrosis and neutrophils recruitment in group treated with 100 pmol of trimer aptamer (Figure 7(a)).…”
Section: Resultssupporting
confidence: 54%
“…The pathogenic effects of meningococcemia, particularly on the skin have previously been attributed to circulating LPS [1], [33], [34]. In this model, non-adherent bacteria, despite circulating in the same numbers as the wild type strain and thus releasing similar amounts of LPS and other bacterial compounds, do not trigger cytokine secretion in the human tissue or lead to significant vascular damage.…”
Section: Discussionmentioning
confidence: 90%
“…The study suggested that the bacterial infection can sensitize tissues to the effects of ischemia, effectively lowering the threshold to acquiring irreversible cell injury (see Table 2). 75 The "two-hit" experimental model of sepsis, DIC, and netosis…”
Section: Pathophysiology Of the Shwartzman-like Reactionmentioning
confidence: 99%